Carotid endarterectomy: guidelines versus real-world practice - Teixeira,Gabriela (2019)
Introduction: A number of guidelines for the management of carotid disease are available to help clinicians in therapeutic decision and provide useful guidance for the best care of the patients. They stated that carotid endarterectomy (CEA) has some benefit in symptomatic patients with carotid stenosis of 50-69% and is highly beneficial in stenosis of 70-99%, with mortality/ stroke rate less than 6%. The maximum benefit is observed when surgery is performed within two weeks after the cerebrovascular event. CEA in asymptomatic patients should be offered to patients with life expectancy higher than 5 years, stenosis of >70%, and perioperative complications should be less than 3%. The aim of this study is to analyse our clinical practice, review treated patients and referral times and compare the outcomes of our institutional practice with published guidelines. Materials and Methods: Retrospective study of patients undergoing carotid endarterectomy at Centro Hospitalar Universitário do Porto between 2010 and 2015. Results: Between 2010 and 2015, 404 patients underwent CEA, 76% men, and mean age 69 years for both sexes. The degree of stenosis was usually evaluated by ultrasound. The use of complementary study with angio-CT was required in 20% and angiography in 2.2% of the cases. The majority of patients (54.2%) were symptomatic (stroke/ TIA <6 months). In patients with a cerebrovascular event diagnosed at our institution, the time to surgery was 10 days (median). All CEA were performed under general anaesthesia and for arterial closure, a Dacronpatch was systematically used. Shunt was used in 4.6% of cases (n=18). The mean surgery time was 101 minutes and the mean clamping time was 40 minutes. Reversal of antioagulation with protamine was performed in 48.3% patients. Morbimortality: 9 post-operative sequelae events (major stroke), 8 minimal / transient deficit (minor stroke) and 4 deaths. In symptomatic patients (n = 219), the rate of postoperative major stroke was 3.6%. In asymptomatic patients (n = 185), a major and a minor stroke was observed (1.1%). Other complications: haematoma 5.9% (n=24); infection 0.2% (n=1); peripheral nerve dysfunction 8.7% (n=35); false aneurysm 0.5% (n=2). Conclusions: Our results are within the reference values. This study allowed us to know our reality, our ability to give an effective answer for our patients, and to serve as a basis for improving ways of acting.